2017
DOI: 10.3389/fcell.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA, Metastasis, and the Mitochondrial Unfolded Protein Response (UPRmt)

Abstract: While several studies have confirmed a link between mitochondrial DNA (mtDNA) mutations and cancer cell metastasis, much debate remains regarding the nature of the alternations in mtDNA leading to this effect. Meanwhile, the mitochondrial unfolded protein response (UPRmt) has gained much attention in recent years, with most studies of this pathway focusing on its role in aging. However, the UPRmt has also been studied in the context of cancer. More recent work suggests that rather than a single mutation or alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Having previously demonstrated that nuclear (34) and mitochondrial (11,16) genetics could alter the efficiency of mammary tumor development and metastasis, we sought to distinguish the impact of stromal contributions in metastatic colonization. Accumulating data implicate mitochondrial function (9,27,(35)(36)(37) and localization (38) in the metastatic process. Because metastasis involves a complex interplay between tumor cells and stroma, including bidirectional signaling and recognition between cells, matrices, and soluble factors, our experimental design kept nuclear and mitochondrial genomes constant between tumor cells and mice, while changing the mitochondria only in the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Having previously demonstrated that nuclear (34) and mitochondrial (11,16) genetics could alter the efficiency of mammary tumor development and metastasis, we sought to distinguish the impact of stromal contributions in metastatic colonization. Accumulating data implicate mitochondrial function (9,27,(35)(36)(37) and localization (38) in the metastatic process. Because metastasis involves a complex interplay between tumor cells and stroma, including bidirectional signaling and recognition between cells, matrices, and soluble factors, our experimental design kept nuclear and mitochondrial genomes constant between tumor cells and mice, while changing the mitochondria only in the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no solid evidence implicating mutations in mtDNA as drivers of tumor formation; however, there are some nonrandom tumor progression-associated changes in mtDNA reported for some tumor types (26, 45, 46). Thus, mtDNA is more likely a contributor to controlling tumor latency or metastasis predicated on active mitochondrial-nuclear cross-talk.…”
Section: Discussionmentioning
confidence: 99%
“…Another important observation is that mutations in OXPHOS genes and accumulation of ROS can lead to the oxidation of proteins and their missfolding. To balance this, metastatic cells show high expression of the unfolded protein response (UPR mt ), which allows them to survive in this highly stressed environment (45,52).…”
Section: Mitochondria Variants and Cancermentioning
confidence: 99%
“…The overexpression of genes involved in the activation of the UPR mt has also been observed in metastatic cells. The UPR mt system protects from protein misfolding and oxidation; however, it might also maintain deleterious mtDNA mutations conferring advantages that facilitate cancer cell metastasis (52,82).…”
Section: Mitochondria Variants and Cancermentioning
confidence: 99%